2006
DOI: 10.1111/j.1365-2990.2006.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the serotonin transporter in the prefrontal cortex in late‐life depression and Alzheimer's disease with and without depression

Abstract: Previous studies investigating the serotonin transporter (SERT) in depression have been inconsistent and included a large proportion of subjects who had committed suicide. In Alzheimer's disease studies have generally reported a reduction in SERT density but have not compared Alzheimer's disease subjects with and without comorbid major depression. We conducted a post mortem study of SERT density in the prefrontal cortex in normal elderly, a group of elderly depressed subjects and in Alzheimer's disease subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 44 publications
(54 reference statements)
0
26
1
1
Order By: Relevance
“…This is the first study showing an elevated SLC6A4 mRNA expression level in leukocytes from AD patients. Although the result of our study was not consistent with previous studies performed by Thomas et al [31] or Chen et al [32] who examined postmortem AD brains, we should consider differences in genotype and allele frequencies, psychological symptoms, and tissues. Therefore, our results must be confirmed in other races including Caucasians.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This is the first study showing an elevated SLC6A4 mRNA expression level in leukocytes from AD patients. Although the result of our study was not consistent with previous studies performed by Thomas et al [31] or Chen et al [32] who examined postmortem AD brains, we should consider differences in genotype and allele frequencies, psychological symptoms, and tissues. Therefore, our results must be confirmed in other races including Caucasians.…”
Section: Discussioncontrasting
confidence: 56%
“…Although previous studies consistently demonstrated that SLC6A4 mRNA levels in leukocytes are significantly higher in patients with MDD compared to healthy controls [29,30], the mRNA expression level in leukocytes from AD patients has not been examined yet. Thomas et al [31] reported that expression of serotonin transporters in the prefrontal cortex is lower in postmortem AD brains from patients both with and without depression than in brains of healthy subjects. Chen et al [32] examined protein and mRNA levels of the serotonin transporter in postmortem prefrontal cortex and showed that levels are reduced significantly in AD compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin is well documented to play a significant role in the pathophysiology of nonvascular major depression and other psychiatric disorders. Conversely, neuropathological studies in late-life depression did not find evidence of a loss of serotoninergic neurons in the dorsal raphe nucleus (Hendricksen et al, 2004) or reduction in serotonin transporter density at the level of the prefrontal cortex (Thomas et al, 2006). However, membrane excitability of pyramidal neurons is not or is poorly modulated by serotonin (Gerdelat-Mas et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Cependant, d'autres résultats viennent contredire ou tempérer ces hypothèses. Par exemple, concernant l'hypothèse sérotoninergique, une étude a montré que la dMA n'était pas corrélée à la perte neuronale dans le noyau du raphé dorsal [52] et une autre, plus récente, que la dMA n'était pas associée à une perte plus importante du transporteur de la sérotonine par rapport à la perte constatée chez des sujets présentant une MA sans dépression [53].…”
Section: Physiopathologie De La Dmaunclassified